The Evolution of Begging Competition, Cooperation and Communication - Wright, Jonathan.; Leonard, Marty L. (Springer Netherlands, 2002)
Begging by nestling birds has become the model system for investigating evolutionary conflicts of interest within families and their theoretical resolution provided by honest signals of offspring need. In response to the recent explosions of scientific papers on the revolution of begging; we have brought together twenty-four original contributions from major researchers in all areas of this dynamic field. Organised into six sections: I: Theoretical approaches; II: Begging as a signal; III: Nestling physiology; IV: Sibling competition; V: Brood parasitism; and VI: Statistical approaches; this book is primarily aimed at research scientists and those at the graduate student level. For the first time, the theoretical and empirical literature on begging is fully reviewed. New ideas and data are also presented from a wide range of natural systems, and each chapter ends with suggestions for future study.